The correlation between intelligence and competitive activities of elite female handball players - Strykalenko, Y.; Shalar, O.; Huzar, V.; Voloshinov, S.; Yuskiv, S.; Silvestrova, H.; Holenko, N. (Journal of Physical Education and Sport, 2020)
Performing complex tactical routines in handball, in variable game situations, necessary displaying anunderstanding the actions and movements requires a great deal of athlete`s intellectual readiness. .Aim: to investigate the influence of intellectual qualities on the efficiency of elite female handball players` competitive activity. Materials and methods: the study was conducted on the basis of women team of Super League, bronze medalist of the Handball Championship of Ukraine. In accordance with the aim, using the Culture Free Intellect Test (CFIT) and INTEST computer test, the level of intellectual qualities of female handball players was investigated. Using developed by coaching staff of Handball Club (HC) "Dnipryanka" team methods for determining useful activities, the features and efficiency of handball players' playing functions were studied and the correlation between these indexes was determined. Experimental study was conducted during the 2018-2019 season. Results: it was found that according to CFIT method the highest result in intellectual qualities backs showed - 95 points, centres - 92 points, wings showed satisfactory level - 89 points, and average IQ of the team was within 92 points. According to the results of the INTEST there is substantial advantage in logical and operational thinking demonstration, namely the backs showed 100 %, pivots also showed 100 % and centres - 95 %. The backs were slightly lower in efficiency. The effectiveness of competitive activity in the team was following: the most effective players are wings (9.5 points), virtually the same result was shown by pivots (9.4 points) (8,9 %) and centres (7,8 points). Goalkeepers` efficiency ratio was 7,5 points. Conclusions: it was found that there is the correlation between level of intellectual qualities development and competitive activity efficiency of elite female handball players. Backs have the highest correlation between IQ indexes according to CFIT and efficiency of competitive activity (r=0,765), but centres have the highest correlation relations between indexes of competitive activity efficiency and associative (r=0,616) and operational (r=0,818) thinking. The goalkeepers to play effectively need high level of abstract thinking (r=0,702). The correlation between efficiency of the performing competitive activities and intellectual qualities display of the other positions is minor.